2020
DOI: 10.1186/s12879-020-05014-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clostridium difficile isolates and the burden of hospital-acquired Clostridium difficile infection in a tertiary teaching hospital in Chongqing, Southwest China

Abstract: Background: Clostridium difficile infection (CDI), especially hospital-acquired Clostridium difficile infection (HA-CDI), continues to be a public health problem and has aroused great concern worldwide for years. This study aimed to elucidate the clinical and epidemiological features of HA-CDI and the characteristics of C.difficile isolates in Chongqing, Southwest China.Methods: A case-control study was performed to identify the clinical incidence and risk factors of HA-CDI. C. difficile isolates were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
1
2
0
1
Order By: Relevance
“…The VIDAS GDH assay is useful for the initial screening of C. difficile. Current findings were consistent with those of Borali and Giacomo 20 , Pechal et al 21 and Dai et al 17 that age, treatment with cephalosporins, clindamycin, or broad-spectrum penicillin are associated with an increased risk of AAD. However, gender was not associated with a difference in AAD frequency.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The VIDAS GDH assay is useful for the initial screening of C. difficile. Current findings were consistent with those of Borali and Giacomo 20 , Pechal et al 21 and Dai et al 17 that age, treatment with cephalosporins, clindamycin, or broad-spectrum penicillin are associated with an increased risk of AAD. However, gender was not associated with a difference in AAD frequency.…”
Section: Discussionsupporting
confidence: 91%
“…Zahar et al 15 reported that CDI was responsible for 14.5% of cases of nosocomial diarrhea by ELISA testing and culture. C. diff strains were isolated in 11% of adult patients, as reported by Karanika et al 16 , but Dai et al 17 reported that the incidence of CDI was almost 31% of the total patients who developed AAD. These variations likely arise from differences in population selection and the sensitivity of laboratory tests.…”
Section: Discussionmentioning
confidence: 81%
“…The three isolates of RT 085 were detected in three different wards of the same hospital in the eastern province of Algeria (Batna), but were missing in the two other provinces; suggesting a possible distinct geographic distribution of this ribotype in Algeria. Although, the ribotype RT 085 was reported as more common in China [33], it was rarely reported in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…У країнах Азії, зокрема у Китаї, останні дослідження показують таку саму захворюваність на CDI, як і в європейських країнах. Нові дослідження, проведені показали захворюваність CDI на рівні 31,1 % [7]. В Україні офіційна реєстрація CDI відсутня, тому відсутні і офіційні показники захворюваності, а також смертності.…”
unclassified